Trends and Developments in Inclusive Sports: A Bibliometric Perspective from Sports Sociology - Rahman, Revanza Rizky; Fitri, Mustika; Suherman, Adang; Apriady, Hilmy (Universitas Negeri Semarang, 2024)
Sports sociology, particularly in the context of inclusive sports, has become an important field in understanding social dynamics in an increasingly diverse modern society. Inclusive sports aim to accommodate various groups with different characteristics, such as people with disabilities, gender minorities, and specific age groups. This article uses bibliometric analysis to explore the development of research on sports sociology in inclusive sports. Through literature mapping obtained from the Scopus database, this research shows a significant increase in publications related to inclusive sports between 2013 and 2023, analyzing data from 794 articles published in various scientific journals.The analysis results reveal the dominance of topics related to